Assessment of the effectiveness of financial internal control systems in public organizations in Tanzania - Ulumbi, Kitundu (Mzumbe University, 2024)
A dissertation submitted to the School of Business in partial fulfillment of the requirements for the award of the degree of Masters of Business Administration-Corporate Management of Mzumbe University